The Effect of Project-Based Learning Model on Student Learning Outcomes on Colloidal Material - Utami, Ajeng Tri; Feronika, Tonih; Wardani, Miessya (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Since students are given the chance to participate directly in their education, project-based learning can enhance their learning results in chemistry, a subject that is considered challenging. Determining the impact of the PjBL model on student learning outcomes for colloidal material is the goal of this study. This study's approach is a quasi-experiment. Two classes—XI IPA 1 and XI IPA 2—that were chosen through purposive sampling made up the research sample. The instrument used in this study is a valid and reliable multiple-choice test of colloidal material. Based on the findings, it can be concluded that the average posttest score for the project-based learning model differs from that of the traditional learning model. According to the posttest results, the experimental class's average score was higher—86.27—than the control class's, which was 76.73. Thus, it can be said that the project-based learning methodology has an impact on students' learning outcomes when it comes to colloidal content.